THE INFLUENCE OF MOTIVATION AND PROFESSIONAL PERCEPTION OF CAREER IN TAXATION OF FEB STUDENTS OF PGRI ADI BUANA UNIVERSITY OF SURABAYA FOR CAREER IN TAXATION - Afrizal, Moh Afrizal Miradji; Adi, Bayu (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Students There are those who want to work As civil servants, there are those who want to be entrepreneurs, all of them need someone who wants to have their own office. As a researcher, I would like to research if students research and want to have a professional career in the taxation field, considering that a career in the taxation profession is generally well-paid for reasons of economic considerations considering that business opportunities in taxation are very wide and promising, including: becoming a tax employee in the environment. The Directorate General of Taxes, becomes a Tax Planner at the Public Accounting Firm (KAP), becomes a Tax Adviser at the Tax Consultant Office, becomes a tax auditor in the company, becomes an employee while in the accounting field who master taxation can establish an independent tax consultant office. Researchers examine professional motivation careers and their perceptions in careers at FEB students of PGRI Adi Buana University Surabaya The result: Accepted (H1) which states that motivation (X1) shows that the interaction between Motivation and Career in the field of Taxation shows a = 0.975 with a significant level with ρ = 0.197> 0.05 H2: There is an influence from the perception of career quality of accounting students for a career in taxation that the perception of career (X2) has a positive effect on a career in taxation in influencing the performance of leaders (y), because the results of hypothesis testing show that the interaction of perceptions A career with a career in taxation shows a positive effect of 92.885 with a significance level or ρ = 0.098> 0.05 H3 is accepted, which states that motivation (X1), career perception (X2) has a positive effect on a career in taxation (y) because of the test results. The hypothesis shows that the interaction between Motivation and Perceptions of a Career Career in the field of Taxation simultaneously shows a positive number of 98.887 with a significance level or ρ = 0.055